Informe De Pasantía En La Empresa Nestlé De Colombia (2023)
This report summarizes the activities that were carried out in the Nestlé de Colombia S.A company during a period of six months as an intern since it was carried out from August 15, 2022 in the area of foreign trade with the position of logistics as an intern, where the academic and professional knowledge obtained throughout the International Trade career was put into practice, thus addressing a series of studies where we will explain the functions and processes that were carried out.